Long‐term effects of prenatal progesterone exposure: neurophysiological development and hospital admissions in twins up to 8 years of age. (9th August 2016) - Vedel, C.; Larsen, H.; Holmskov, A.; Andreasen, K. R.; Uldbjerg, N.; Ramb, J.; Bødker, B.; Skibsted, L.; Sperling, L.; Krebs, L.; Zingenberg, H.; Laursen, L.; et al.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2016; 48: 284–284 ABSTRACT: Objectives: To perform a neurophysiological follow‐up at 48 or 60 months of age in children exposed prenatally to progesterone compared with a placebo and evaluate their medical histories up to 8 years of age. Methods: In this study, Danish participants of the PREDICT study, including 989 surviving children from 498 twin pregnancies, were followed‐up. PREDICT was a placebo‐controlled randomized clinical trial examining the effect of progesterone for prevention of preterm delivery in unselected twin pregnancies. Medical histories of the children were reviewed and neurophysiological development was evaluated by the parent‐completed Ages and Stages Questionnaire (ASQ) at either 48 or 60 months after the estimated date of delivery. We used the method of generalized estimating equation to account for the correlation within twins. Results: A total of 492 children had been exposed prenatally to progesterone and 497 to placebo. There was no difference in the number of admissions to or length of stay in hospital between the treatment groups, and we found no overall difference in the rates of diagnoses made. However, the odds ratios (ORs) for a diagnosis concerning the heart was 1.66 (95% CI, 0.81–3.37), favoring placebo, among all children, 2.38 (95% CI, 1.07–5.30) in dichorionic twins and 8.19 (95% CI, 1.02–65.6) in all children when excluding diagnoses made at outpatient clinic visits. ASQ scores were available for 437 children (progesterone, n = 225; placebo, n = 212). Mean ASQ score was slightly higher in the progesterone group compared with the placebo group ( P = 0.03). In dichorionic twins, the risk of having a low ASQ score (< 10 th centile) was decreased in the progesterone group (OR, 0.34 (95% CI, 0.14–0.86)). Conclusion: Second‐ and third‐trimester exposure of the fetus to progesterone does not seem to have long‐term harmful effects during childhood, but future studies should focus on cardiac disease in the child. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.